Are U.S. food and beverage companies now advertising healthy products to children on television? An evaluation of improvements in industry self-regulation, 2017–2021 - Jensen Madrigal, Melissa Lorena (2023)
Background Through the Children’s Food and Beverage Advertising Initiative (CFBAI), U.S. food companies pledge to only advertise healthier products in children’s television (TV) programming, but previous research shows that highly advertised products do not qualify as nutritious according to independent nutrition criteria. In 2020, the CFBAI implemented stricter nutrition criteria for products that may be advertised to children, but the potential impact of these changes has not been assessed. This observational study evaluates (1) improvements in energy and individual nutrient composition of products that companies indicated may be advertised to children (i.e., CFBAIlisted products) in 2020 versus 2017, (2) amount of advertising on children’s TV for CFBAI-listed versus other products in 2021, and 3) the nutrition quality of advertised versus non-advertised CFBAI-listed products. Methods Data include energy, saturated fat, sodium, and sugar content and overall nutrition quality (Nutrition Profle Index [NPI] scores) of CFBAI-listed products in 2017 (n=308) and 2020 (n=245). Nielsen data provided total ad spend‑ ing and children’s exposure to ads on children’s TV channels for all foods and beverages in 2021. Results From 2017 to 2021, energy, saturated fat and sugar declined for CFBAI-listed products in three of six food categories (yogurt, sweet and salty snacks). Although CFBAI-listed products accounted for 79% of food ads viewed by children on children’s TV channels, just 50% of CFBAI-listed food and 36% of drink brands were advertised on children’s TV. Moreover, advertised products were signifcantly less nutritious than non-advertised CFBAI-listed products. Conclusion Despite revised nutrition standards and improvements in nutrient content of some product categories, participating companies continued to primarily advertise nutritionally poor food and beverages on children’s TV. CFBAI companies have not delivered on their promises to advertise healthier products to children.